The Effectiveness Of Birthing Ball Therapy On The Duration Of The First Stage Of Labor And The Intensity Of Labor Pain In Primigravid Mothers Giving Births - Lilis Suryani; Mufida Dian Hardika (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This type of research is an observational analytic study with a cross-sectional design. The sampling technique used Simple Random Sampling. The sample size was 40 mothers with the division of 20 mothers used birthing ball therapy and 20 mothers did not use birthing ball therapy. Data collection tools were observation sheets. Data analysis was performed using Chi-Square and Multiple Logistic Regression analysis. There was a positive effect of using the Birth Ball with the duration of the first stage of labor of (OR = 5.19; CI = 95%; 1.06 to 25.4; p = 0.042), the use of the Birth Ball with the intensity of labor pain of (OR = 7.57; CI = 95%; 1.53 to 37.3; p = 0.013) and it was statistically significant. The use of a birthball has been shown to be effective in shortening the first stage of labor and reducing the intensity of pain